The Use of Citronella Essential Oil (Cymbopogon nardus) to Treat ORF Disease in Local Sheep - Wahyu Suradi Pranata; Zahrotul Fuadzah; Rizky Prasetiadi; Asep Rahmat Khaerudin; Ai Nurfaridah; Yuga Suwarsa (Jurnal Ternak, 2025)
ORF disease is a contagious skin infection in sheep caused by a virus of the Parapoxvirus genus. The resulting scabby lesions can lead to decreased productivity and secondary infections. This study aimed to evaluate the effectiveness of citronella (Cymbopogon nardus) essential oil in accelerating the healing of ORF wounds. A total of 24 local sheep infected with ORF were divided into three groups: Group I (1% concentration), Group II (5%), and Group III (10%). The treatment solution was applied topically every two days over a 14-day period. The results showed that Group III had the fastest healing time. Citronella essential oil at 10% concentration was proven effective as a natural treatment for ORF and holds potential for further development in veterinary applications for sheep farmers.